One - Oliver, Jamie, 1975- (Flatiron Books, 2023)
"One is the ultimate cookbook that will make getting good food on the table easier than ever before... Jamie Oliver is back to basics with over 120 simple, delicious, ONE pan recipes. In ONE, Jamie Oliver will guide you through over 120 recipes for tasty, fuss-free and satisfying dishes cooked in just one pan. What's better: each recipe has just eight ingredients or fewer, meaning minimal prep (and cleaning up) and offering maximum convenience. Packed with budget-friendly dishes you can rustle up any time, ONE has everything from delicious work from home lunches to quick dinners the whole family will love; from meat-free options to meals that will get novice cooks started. With chapters including ... · Veggie Delights · Celebrating Chicken · Frying Pan Pasta · Batch Cooking Simple dishes like Juicy Tahini Chicken and Hassleback Eggplant Pie and will soon become your new favorites. There are plenty more no-fuss, tasty recipes that make ONE sit alongside 5 Ingredients and Ultimate Veg as your go-to kitchen companions"--